Graphene-based saturable absorber for passive Q-switching erbium doped fiber laser - Jasni, Nur Afiqah Husna; Zuikafly, Siti Nur Fatin; Ahmad, Fauzan; Abdullah, Mundzir; Wan Nawawi, Wan Mohd Fazli; Yahaya, Hafizal (IEEE, 2020)
Q-switched erbium-doped fiber laser integrating graphene-based polymer composite is reported. Electrochemical exfoliation was used to synthesize graphene by immersing two graphite rods in solution containing 1% of sodium dodecyl sulfate (SDS) in de-ionized water. The supply for the electrochemical process is 20 V and the process took around 5 hours to produces suspension containing graphene flakes. The suspension is then mixed with chitin bio polymer composites to develop graphene-chitin film based passive Qswitcher. A small portion of the fabricated film was then integrated in erbium doped fiber laser in ring cavity for pulse laser generation. Pulsed laser with repetition rate of 67.39 kHz with 2.24 μs pulse width was generated. The laser output also has high pulse energy of 108.38 nJ with instantaneous peak power of 45.48 mW.